ANALISIS FRAMING KONTEN TAGAR #TOLAKBASABASIPOLITIK DI AKUN INSTAGRAM @REMOTIVI.OR.ID - Novia, Yandi; Syah, Hakim; Setiawan, Heri (STKIP Pesisir Selatan, 2025)
The presence of social media has implications for political communication in Indonesia. One of the implications is the rise of online political activism, as shown by the hashtag #TolakBasaBasiPolitik by Remotivi on Instagram. Therefore, this article aims to analyze content construction with the hashtag #TolakBasaBasiPolitik using Robert N. Entman’s framing model analysis framework. The data in this study is content using the hashtag #TolakBasaBasiPolitik uploaded to the Instagram account @remotivi.or.id (https://www.instagram.com/remotivi.or.id) between January and February 2024. Four aspects were analyzed in this content: define the problem, diagnose causes, moral judgment, and treatment recommendation. Data collection was conducted through observational documentation. The study found that content with the hashtag #TolakBasaBasiPolitik by Remotivi on Instagram represents a consistently critical stance toward superficial political journalism practices in Indonesia. In other words, content with this hashtag criticizes mainstream media for prioritizing sensational, personal, and visual narratives rather than substantive and educational narratives related to ideas and policies. In this context, crucial issues in democracy are overshadowed by cosmetically oriented political aspects such as debate style, the sensationalization of candidates, or electoral drama.